2009
DOI: 10.1016/j.chembiol.2009.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Two Additional Signaling Molecules in Streptomyces coelicolor and the Development of a Butyrolactone-Specific Reporter System

Abstract: gamma-Butyrolactone bacterial hormones regulate antibiotic production and morphological differentiation in Streptomyces species. One gamma-butyrolactone, SCB1, has been previously characterized in Streptomyces coelicolor. Here we report the characterization of two additional gamma-butyrolactones, named SCB2 (2-[1'-hydroxyoctyl]-3-hydroxymethylbutanolide) and SCB3 (2-[1'-hydroxy-6'-methyloctyl]-3-hydroxymethylbutanolide), possessing an antibiotic stimulatory activity. To elucidate the specificity determinants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 27 publications
1
75
1
Order By: Relevance
“…Its production of antibiotics is regulated by the synthesis of γ-butyrolactones, members of the quorum sensing-type family of signaling molecules [17], [18], which are found in many Streptomyces species, including Streptomyces virginiae [19], Streptomcyes lavendulae [20], [21], and Streptomyces clavuligerus [22]. In S. coelicolor A3(2), three kinds of γ-butyrolactones have been identified which serve to synchronize the onset of antibiotic synthesis within the population [23], [24], [25], among these S. coelicolor butanolide 1 (SCB1) is abundantly found. These SCBs regulate antibiotic biosynthetic clusters controlling synthesis of blue pigmented actinorhodin (Act) [26], red pigmented undecylprodigiosin (Red) [26] and yellow pigment yPCK [27].…”
Section: Introductionmentioning
confidence: 99%
“…Its production of antibiotics is regulated by the synthesis of γ-butyrolactones, members of the quorum sensing-type family of signaling molecules [17], [18], which are found in many Streptomyces species, including Streptomyces virginiae [19], Streptomcyes lavendulae [20], [21], and Streptomyces clavuligerus [22]. In S. coelicolor A3(2), three kinds of γ-butyrolactones have been identified which serve to synchronize the onset of antibiotic synthesis within the population [23], [24], [25], among these S. coelicolor butanolide 1 (SCB1) is abundantly found. These SCBs regulate antibiotic biosynthetic clusters controlling synthesis of blue pigmented actinorhodin (Act) [26], red pigmented undecylprodigiosin (Red) [26] and yellow pigment yPCK [27].…”
Section: Introductionmentioning
confidence: 99%
“…1A), discovered as the first example in the early 1960s, which triggers both streptomycin production and sporulation in Streptomyces griseus (4,5). Fourteen γ-butyrolactone autoregulators have since been identified in several Streptomyces species (3,6). At least 60% of Streptomyces species appear to synthesize this type of signaling molecule (7), whereas signaling molecules produced by many other species still remain to be unraveled, largely because of extremely low concentrations in the culture medium.…”
mentioning
confidence: 99%
“…Recognition of the signalling molecule occurs through the C-terminal region of the protein [24 ]. A recent publication [25] has shown that the GBL core directly interacts with the binding pocket of the receptor, implying that this structure is responsible for the recognition of the GBL, whereas the n-alkane C 2 residue may be responsible for the specificity of the binding, and therefore the threshold concentration necessary to perform the switch-like transition, as previously suggested by Hsiao et al [26].…”
Section: The Gbl Signalling Circuitsmentioning
confidence: 68%
“…A functional AdpA homologue is also found in other Streptomyces species, such as in Streptomyces coelicolor, where it was recently shown that, in contrast to what has been reported for S. griseus, the AdpA acts as a positive self-regulator [33]. However, in S. coelicolor antibiotic production is not regulated by A-factor GBL, but by the GBLs SCB1-3 [26,29] (Figure 1c). Their synthesis involves the ScbA protein, whose gene is encoded divergently from the GBL receptor, ScbR.…”
Section: The Gbl Signalling Circuitsmentioning
confidence: 86%